IMPLEMENTASI KEBIJAKAN PUBLIK DALAM PERSPEKTIF CHARLES O. JONES: SUATU TINJAUAN KONSEPTUAL - Fadhil; Bahagia (Jurnal Metrum, 2025)
Policy implementation is a crucial phase in the public policy cycle, determining program success or failure. This article aims to analyse the implementation process using Charles O. Jones's framework, which includes three core components: organising, interpreting, and applying. Utilising a literature review method, this study examines theoretical insights and relevant empirical studies, particularly within the Indonesian context. The findings indicate that policy implementation effectiveness is significantly influenced by organisational structure, resource capacity, actor communication, and local political dynamics. The article underscores the importance of contextual and participatory approaches in public policy implementation.